2006
DOI: 10.1111/j.1460-9568.2006.04860.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐active neurons in the preoptic area project to the hypothalamic paraventricular nucleus and perifornical lateral hypothalamus

Abstract: The lamina terminalis consists of the organum vasculosum of the lamina terminalis (OVLT), median preoptic nucleus (MnPO) and subfornical organ. The MnPO and ventrolateral preoptic area (vlPOA) are known to contain high densities of neurons that are sleep active. The prevalence of sleep-active neurons in the OVLT and subfornical organ is unknown. The vlPOA and subdivisions of the lamina terminalis project to hypothalamic regions involved in the control of behavioral, electrographic or autonomic arousal, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 58 publications
2
68
0
1
Order By: Relevance
“…Recent anatomical studies showed that the MnPN input to the PF/LH is one of the heaviest among the structures involved in control of behavioral states (Yoshida et al, 2006). MnPN-PF/LH projection neurons include a subset of cells exhibiting sleep-related c-Fos immunoreactivity (Uschakov et al, 2006). These findings allow us to hypothesize that MnPN plays an important role in sleeprelated inhibitory modulation of hypocretin and nonhypocretin arousal-related PF/LH neurons.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent anatomical studies showed that the MnPN input to the PF/LH is one of the heaviest among the structures involved in control of behavioral states (Yoshida et al, 2006). MnPN-PF/LH projection neurons include a subset of cells exhibiting sleep-related c-Fos immunoreactivity (Uschakov et al, 2006). These findings allow us to hypothesize that MnPN plays an important role in sleeprelated inhibitory modulation of hypocretin and nonhypocretin arousal-related PF/LH neurons.…”
Section: Introductionmentioning
confidence: 88%
“…If these projections originate in sleep-related cells, they are expected to be excitatory. Activation of GABA/galaninergic VLPO neurons projecting to the PF/LH Uschakov et al, 2006;Yoshida et al, 2006) is likely to be a complementary mechanism of inhibitory control of PF/LH arousal network.…”
Section: Effects Of the Mnpn On Pf/lh Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of testable hypotheses has been recently proposed. 4 The lower values of SNA to the skeletal muscles and kidneys during NREM sleep compared with wakefulness may result from: (a) inhibition of a "stress pathway" that involves the hypothalamic paraventricular nucleus, 21 a master autonomic and endocrine controller; 22 (b) inhibition of a "command neuron" pathway that involves the pedunculopontine nucleus of the rostral pons, 23,24 part of the mesencephalic locomotor region; 25 and (c) potentiation of a "baroreflex pathway" 26 that involves the pontine parabrachial nucleus 27 and the medullary nucleus of the solitary tract. 28 The lower values of skin SNA during NREM sleep compared with wakefulness may result from inhibition of a "thermoregulatory pathway" for heat generation and retention, which includes the hypothalamic median preoptic nucleus, the hypothalamic medial preoptic area, and the rostral medullary raphe.…”
Section: Cardiovascular Control During Nrem Sleepmentioning
confidence: 99%
“…MnPO neurons project to the DRN and LC. MnPO and VLPO neurons that express sleep-related c-Fos project to the HCT neuronal field in the lateral hypothalamus [64]. Sleep-active neurons in VLPO and MnPO exhibit discharge profiles across the wake-NREM-REM cycle that are reciprocal to those of wakepromoting HA, 5HT, NE, and HCT neurons [63] .…”
Section: Sleep Onset and Nrem Sleep-promoting Mechanismsmentioning
confidence: 99%